The Influence of Leadership Style, Workload, and Work Stress on Employee Performance - Pratiwi Liberti; Sisi Wardani (Yayasan Az Zukhruf Cendikia, 2025)
Purpose – This study aims to examine how leadership, workload and work stress employee performance Design/methodology/approach – This research uses the approach of quantitative approach using primary data collected from one company PT Mayora Indah in Cibitung. Data analysis was performed using Partial Least Square (PLS) Findings – The findings reveal that leadership style has a positive and significant effect on employee perfomance, workload has a positive and significant effect on employee performace, and work stres has a negative and significant effect employee performance Research limitations/implications – This research can be an input for PT Mayora Indah in improving employee performance. This research also discusses the importance of effective leadership style, balanced workload, and good stress management.